2020
DOI: 10.1038/s41598-020-71288-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, virulence genes, and antimicrobial resistance of Vibrio species isolated from diseased marine fish in South China

Abstract: Here, 70 potential Vibrio pathogens belonging to nine species, dominated by Vibrio harveyi, were isolated and identified from diseased aquacultured marine fish in South China. Subsequently, the prevalence of 11 virulence genes and the resistance to 15 antibiotics in these strains were determined. Most strains possessed atypical virulence genes in addition to typical virulence genes. Notably, hflk and chiA originating from V. harveyi, and flaC associated with V. anguillarum were detected in more than 40% of aty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 37 publications
4
44
1
Order By: Relevance
“…This hypothesis is further sustained by the presence of MDR and XDR in a large proportion ( Table 3 ). Deng et al (2020) [ 66 ] isolated Vibrio species, with a high prevalence of resistance to vancomycin, amoxicillin, midecamycin, and furazolidone, moderate prevalence of resistance to tobramycin, rifampicin, gentamicin, and tetracycline, and low prevalence of resistance to erythromycin, trimethoprim–sulfamethoxazole, doxycycline, and chloramphenicol. We found similar results for penicillins, but not for tetracyclines and erythromycin, were the results showed the opposite, with low and high prevalence of resistance, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is further sustained by the presence of MDR and XDR in a large proportion ( Table 3 ). Deng et al (2020) [ 66 ] isolated Vibrio species, with a high prevalence of resistance to vancomycin, amoxicillin, midecamycin, and furazolidone, moderate prevalence of resistance to tobramycin, rifampicin, gentamicin, and tetracycline, and low prevalence of resistance to erythromycin, trimethoprim–sulfamethoxazole, doxycycline, and chloramphenicol. We found similar results for penicillins, but not for tetracyclines and erythromycin, were the results showed the opposite, with low and high prevalence of resistance, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Aquaculture is currently recognised as the fastest growing food producing sector globally, and sustainable development of aquaculture practices is very crucial to assure food ssecurity and strengthen the global economy (Olsen and Hasan, 2012). On the other hand, excessive industrialized practices and over-intensive exploitation for boosting the production, has led to the emergence of serious bacterial disease outbreaks in aquaculture (Deng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Vibriosis is the most prevalent one among different bacterial diseases, and affects a wide range of marine and estuarine fish species (Chatterjee and Haldar, 2012). Among the various Vibrio spp., V. vulnificus, V. parahaemolyticus and V. harveyi represent the most frequent fish pathogens causing substantial economic losses to marine or estuarine aquaculture practices (Ruwandeepika et al, 2010;Deng et al, 2020). Apart from aquaculture perspectives, these bacteria have emerged as a causative agent of many foodborne, waterborne and zoonotic diseases in humans (Sapkota et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Vibrio is usually reported being related to food-borne diseases and aquaculture diseases. Diseases or even death of aquatic animals caused by Vibrio infection have been reported worldwide and are showing an increasing trend [7,11,18,67]. Therefore, Vibriosis has caused significant impacts on human health and the development of aquaculture [68][69][70].…”
Section: Pathogenicity Of Vibriomentioning
confidence: 99%
“…However, high-density farming, severe human activities and global climate change have led to frequent Vibriosis, which has posed a huge threat to human health and social and economic development [17]. Vibriosis is one of the most common bacterial diseases affecting a variety of marine fish and shellfish [18,19]. Studies have demonstrated that the content of Vibrio in aquaculture facilities is very high, especially during the outbreak of disease.…”
Section: Introductionmentioning
confidence: 99%